The different expressions of urokinasetype plasminogen activator, urokinasetype plasminogen activator receptor, and plasminogen activator inhibitor-1. Several scores of cell pleomorphism, number of mitosis and keratiniza - Irianiwati, Ahmad Ghozali Totok Utoro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Urokinase plasminogen activator (uPA) system plays important role in cancer invasion and metastasis. The real function of PAI-1 is to protect extracellular matrix from degradation. But, there are still arguments about the function of PAI-1. In colorectal cancer, breast cancer, and liver cancer, high expressions of uPA and PAI-1 are related to poor prognosis of the patients. In squamous cell carcinoma of the cervix, the role of uPA system in its relation with histological grading (consists of several scores of cell pleomorphism, number of mitosis and keratinization index) are still unclear.Aim: To find out the different expressions of uPA, uPAR, PAI-', and ratio of uPA!PAI-1 among several scores of cell pleomorphism, number of mitosis and keratinization index of cervical cancerMethods: Thirty five paraffin blocks of squamous cell carcinoma of the cervix were grouped histologically based on the score of cell pleomorfism, number of mitosis, and keratinization index. The specimens were stained immunohistochemically with MoAb against uPA, uPAR, and PAI-1 with chromogen DAB and counterstain Meyer Hematoxyllin. The expression of uPA, uPAR, PAI-1, and ratio of uPA/PAI-1 were counted based on the number of positive expression tumor cells!100 tumor cells in five microscopic fields. The different expression of each variable will be analyzed with One Way Anova analysis.Result: There were statistically insignificant differences between the expressions of uPA, uPAR, PAI-1, and ratio of uPA/PAI-' based on the score of cell pleomorfism (p = 0.463, 0.731, 0.541, 0.460, respectively), keratinization index (p = 0.207, 0.062, 0.231, 0.576, respectively), and nlimber of mitosis (p = 0.359, 0.125, 0.428, 0.340, respectively) of squamous cell carcinoma of the cervix.Conclusion: The result suggested that the expressions of uPA, uPAR, PAI-1, and ratio of uPA/PAI-1 did not have important roles in cells pleomorfism, number of mitosis, and keratinization index of cervical cancer.Key words: uPA - uPAR - PAI-' - ratio of uPA!PAI-1 - cell pleomorphism - number of mitosis - keratinization index - cervical cancer